A high latitude Devonian lungfish, from the Famennian of South Africa - Gess, Robert W. (PeerJ, 2019)
New fossil lungfish remains comprising two parasphenoids, tooth plates and scales from the Famennian Witpoort Formation of South Africa are described. From the parasphenoid material, which bears similarity to Oervigia and Sagenodus but is nevertheless unique, a new genus, Isityumzi mlomomde gen. et sp. nov. is erected. Tooth plates and scales from the same locality may be conspecific but are not yet assigned until further material becomes available. The tooth plates closely resemble those of some taxa in the Carboniferous genus Ctenodus. The new taxon is significant as only the second Devonian lungfish described from the African continent, and for hailing from the high-latitude (polar) Waterloo Farm environment situated close to 70° south during the Famennian.